Mathematical model of a loaded conical antenna excitation - Doroshenko, V. A.; Shimuk, Y. D. (Видавництво Національного університету "Львівська політехніка", 2009)
Electromagnetic wave scattering problems for the imperfectly conducting cones are considered. Boundary impedance conditions including the cone curvature parameters are used. Analytical solutions for some partial cases are obtained. The surface curvature parameters effects on the problems solutions are studied.
Keywords: semi-transparent cone; impedance surface; initial boundary problem; rigorous methods; boundary conditions